Invisibilised dirty work: The multiple realities of US airline pilots' work. Issue 2 (15th March 2017) - Fraher, Amy L.
ABSTRACT: This paper builds upon Heather Höpfl's intellectual contributions in the areas of identity, dirt, and study of the unseen at commercial air carriers, by examining US airline pilots' work over the decade between 2000 and 2010. Challenging assumptions about pilots being an elite group of unemotional professionals, findings here reveal how a once prestigious profession devolved into 'invisibilised dirty work' in the occupational rhetoric of employees. In contrast to dirty work definitions in which the associated taint is static, externally applied, and predates employees' entry into their occupation, this study finds pilots' emotional dirty work involves a changed sense of occupational identity due to industry restructuring and increased managerialism in which employees were forced to perpetuate a charade of safety in a system they believe has become increasingly risky.